2009
DOI: 10.1039/b916581a
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin tough double network hydrogels showing adjustable muscle-like isometric force generation triggered by solvent

Abstract: Ultrathin double-network hydrogels, which have super-high toughness under micro-scale thickness (elastic elongation epsilon(b) > 1000%, tensile strength sigma(b) > 2 MPa and tearing energy G approximately 600 J m(-2)), and solvent-triggered fast and high isometric stress generation, were synthesized by coupling the salt-controlled swelling process and polymer chain pre-reinforced technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 35 publications
(10 reference statements)
0
67
0
Order By: Relevance
“…71 Entanglements between two polymer networks are a prerequisite condition in all cases for the toughness of DN gels. 75 After the innovation of DN gels, some research groups began studying various avenues of research with DN gels, but no detailed observations of stimuli sensitivity have been reported thus far, except in the work of Liang et al 76 Recently, they reported a fast and high solvent-triggered force generation considering their mechanical toughness for very thin DN gels. As high-level inhomogeneities are the origin of superior toughness of DN gels, the stimuli sensitivity of bulk DN gels could be very complex.…”
Section: Double Network Gelsmentioning
confidence: 99%
“…71 Entanglements between two polymer networks are a prerequisite condition in all cases for the toughness of DN gels. 75 After the innovation of DN gels, some research groups began studying various avenues of research with DN gels, but no detailed observations of stimuli sensitivity have been reported thus far, except in the work of Liang et al 76 Recently, they reported a fast and high solvent-triggered force generation considering their mechanical toughness for very thin DN gels. As high-level inhomogeneities are the origin of superior toughness of DN gels, the stimuli sensitivity of bulk DN gels could be very complex.…”
Section: Double Network Gelsmentioning
confidence: 99%
“…Ultrathin PAMPS/PAAm double-network gels (UTDN gels) are synthesized by multistep photopolymerization (Figure 3), 71 adapted from the general two-step synthesis of bulk DN gel. Using two glass plates spaced with 15, 25, and 50¯m polyethylene film, we first synthesized ultrathin PAMPS gels by the first step polymerization.…”
Section: Thin Film Dn Gel and Its Stimuli-responsive Behavior As Musclementioning
confidence: 99%
“…71 Figure 5a presents the cyclic changes in the isometric stress of the UTDN gels alternately triggered by water and EtOH. The magnification of one of the cycles (8001300 s) is shown in Figure 5b.…”
Section: Thin Film Dn Gel and Its Stimuli-responsive Behavior As Musclementioning
confidence: 99%
“…We have developed a three-step polymerization method to synthesize the thin and tough film hydrogels with triple network (TN) structure based on the tough DN gel principle [20][21][22]. (This gel was called as DN gel in the cited literatures.…”
Section: Introductionmentioning
confidence: 99%
“…Under a certain pre-strain, these hydrogels could be triggered by ethanol, a poor solvent to PAAm network, and gave a high muscle-level stress output of 0.25 MPa with a response time of ~10 seconds [20].…”
Section: Introductionmentioning
confidence: 99%